Music as Environment: Biological and Ecological Constraints on Coping with the Sounds - Reybrouck, Mark (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2018)
This paper deals with musical sense-making in a real-time listening situation. Revolving around the ecological conception of organism-environment interaction, it elaborates on the interactions between the listener as an organism and the music as environment. The listener, in this view, can be described in terms of coping behavior that is shaped by biological and ecological constraints. Relying on the seminal work by von Uexküll and Gibson in the fields of biosemiotics and ecology, with a special emphasis on the concepts of functional tone and affordance, listeners are defined as organisms that actively seek for information by carrying out physical and epistemic interactions on the sonic environment. As such, they construct an inner model of the sonic world as the sum total of subjective meanings that are assigned to those elements that receive semantic weight. By stressing the role of functional significance and interactions, this approach is on a continuum with the biosemiotic claims that music knowledge must be generated as a tool for adaptation to the sonic world. Musical sense-making, in this view, relies on several levels of processing, going from low-level reactivity to higher-level processing by the brain.